Mechanism for the interaction of thiols with methylcobalamin - Frick, T.; Francia, Marie D.; Wood, J.M. (Biochimica et biophysica acta, 1976)
The reaction between methylcobalamin and ethane-thiol sulfonic acid (Coenzyme M) has been studied under aerobic conditions. For this reaction evidence is presented for a catalytic cycle which promotes homolytic cleavage of the Cobalt-carbon σ-bond to give Cob(II)alamin (B12-r) and methylcoenzyme M as the products. This reaction is especially pertinent to our understanding of the mechanism of methane-biosynthesis. In addition, we have used 220 MHz 1H NMR and 13C NMR to show that thiols do not react with methylcorrinoids by displacing the base trans-axial to the cobalt-carbon bond. This NMR study is especially important since the coordination of thiols to cobalt has previously been reported to occur by a number of of researh groups including our own.